2022
DOI: 10.3390/vetsci9100544
|View full text |Cite
|
Sign up to set email alerts
|

Are Horse Owners Able to Estimate Their Animals’ Body Condition Score and Cresty Neck Score?

Abstract: Obesity and overconditioning are becoming more prevalent in horses, and are influencing the animal’s health, activity, and reproductive efficiency. Body condition score (BCS) and cresty neck score (CNS) have been correlated with the development of various diseases. Many of the papers in the literature evaluate the prevalence of obesity and overconditioning in horse populations considering BCS given by owners. The aim of this study was to evaluate the validity of the owners’ estimation of the degree of equine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Horse owners in PEI believed proper weight management was imperative for their horses’ overall health and were aware that equine obesity was associated with various health issues such as laminitis, osteoarthritis, and metabolic diseases (Hitchens et al 2016 ; Furtado et al 2021a ; Busechian et al 2022 ). Despite this, owners commonly chose to keep their horses over- rather than underweight due to their conflicting perceptions about horse weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horse owners in PEI believed proper weight management was imperative for their horses’ overall health and were aware that equine obesity was associated with various health issues such as laminitis, osteoarthritis, and metabolic diseases (Hitchens et al 2016 ; Furtado et al 2021a ; Busechian et al 2022 ). Despite this, owners commonly chose to keep their horses over- rather than underweight due to their conflicting perceptions about horse weight.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, owners have considered underfed or malnourished horses a significant welfare issue (McGowan et al 2010 ) while overlooking the implications of overweight or obese horses (Potter et al 2016 ; Morrison et al 2017 ; Furtado et al 2021a ). Further, owners tend to be less inclined to make management-related decisions for their overweight horses compared to horses that are underweight (Potter et al 2016 ; Morrison et al 2017 ; Furtado et al 2021a ), often perceiving overweight horses to be the result of good horse management practices (Furtado et al 2021a ; Busechian et al 2022 ). However, horse obesity can be detrimental to horse welfare, for example, because of its association with painful and potentially life-threatening conditions (Rioja-Lang et al 2020 ), such as osteoarthritis (Robles et al 2018 ), laminitis/founder (Milinovich et al 2006 ; Frank et al 2010 ) and strangulating lipomas (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…When using BCS as a potential health measure for horses, uniformity in the individual scorings is essential. A study of the validity of subjective body condition scoring methods reported a good correlation in equine BCS data between owners and an experienced veterinarian [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The validity of one of the subjective body condition scoring methods that is based on a 0–5 scale has been evaluated [ 32 ]. The results showed a good correlation between BCS values awarded by owners and an experienced veterinarian.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation